Analisis Kinerja Jaringan Jalan (Studi Kasus : Jln.S Parman Medan) - Deddy Siahaan; Marwan Marwan; Mahliza Mahliza (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2022)
At this time the S Parman road in Medan City is very congested because around the road there are new buildings and indiscriminate parking so that the performance of the roads on S Parman road is increasing.  Thus, S Parman road users need an alternative repair in order to obtain a less congested road.  In general, this study aims to determine the performance of the road network on the S Parman road section.  The method used in this research is based on the 1997 Indonesian Road Capacity Manual (MKJI). The steps to conduct this study are to conduct a traffic survey on the S Parman road, the cambrige intersection on the S Parman - Glugur road and geometric measurements of the road on the S road section.  Parman.  In the existing condition, S Parman road has a DS of 0.73, and Gajah Mada road is 0.70 and KH Zainal Arifin road is 0.69 and the Attorney road is 0.38 and Glugur road is 0.33.  With the DS already approaching the standard limit of 0.73, which is set in the 1997 Indonesian Road Capacity Manual (MKJI) of 0.75, traffic management is needed in order to obtain optimal road performance.